THE IMPACT OF DIGITAL TECHNOLOGIES FOR MONITORING MOTOR ACTIVITY ON ENHANCING THE COMPETITIVE PERFORMANCE OF TRACK AND FIELD ATHLETES IN THE SYSTEM OF HIGHER SPORTS TRAINING - Ubbiyev Baxytbay Amangeldiyevich (Bright Mind Publishing, 2025)
The rapid integration of digital technologies into modern sport has significantly transformed the system of higher sports training, particularly in track and field athletics, where competitive success is closely linked to precise control of motor activity, training load, and recovery processes. This study examines the impact of digital technologies for monitoring motor activity on enhancing the competitive performance of track and field athletes within the context of higher sports training. The relevance of the research is determined by the growing demand for evidence-based training management and the increasing availability of wearable sensors, mobile applications, and analytical platforms capable of providing real-time and longitudinal data on athletes’ physical activity. Digital monitoring tools enable coaches and athletes to obtain objective indicators of movement patterns, intensity, volume, biomechanical parameters, and physiological responses, which significantly improves the accuracy of training planning and performance evaluation. The abstract emphasizes that traditional training approaches, largely based on subjective assessment and generalized norms, are increasingly insufficient in elite and university-level sport, where marginal gains determine competitive outcomes. The study synthesizes contemporary theoretical perspectives and empirical findings related to digital monitoring technologies and their role in optimizing training processes, preventing overtraining, and supporting individualized athlete development. Special attention is given to the pedagogical dimension of higher sports training, where digital tools function not only as instruments of control but also as means of developing athletes’ self-regulation, reflective skills, and professional competencies. The research highlights the potential of digital monitoring systems to bridge the gap between training practice and sports science by translating complex data into actionable coaching decisions. The expected outcomes include improved competitive performance, enhanced training efficiency, and increased sustainability of athletic development. Overall, the study contributes to the understanding of how digital technologies can be systematically integrated into higher sports education and training to support the holistic development of track and field athletes and to improve their competitive effectiveness in a rapidly evolving digital sports environment.
Keywords: Digital technologies, motor activity monitoring, track and field athletics, competitive performance, higher sports training, wearable sensors, training load control, performance analytics, athlete monitoring systems.